Comparison of Different Final Impression Techniques for Management of Resorbed Mandibular Ridge: A Case Report - Bhupender Yadav; Manisha Jayna; Harish Yadav; Shrey Suri; Shefali Phogat; Reshu Madan (Hindawi Limited, 2014)
The history of complete denture impression procedures has been influenced largely by the development of impression materials from which new techniques and ideas arose. The purpose of this study was to compare the retention of complete dentures made by using different impression techniques like conventional, admixed, all green, and functional techniques. The results showed that there was significant difference in retention between the six techniques where functional technique showed the highest mean value of retention followed by elastomeric, all green, and admixed, while cocktail and green stick compound showed the lowest mean value. However, on clinical examination, the retention produced by the six techniques was satisfactory.